Role of Indian Medicinal Plants for Immunity Booster Against SARS-CoV-2 Infection: An Updated Review - Verma, Kavita; Mishra, Yoganchal; Kapoor, Neha; Yadav, Neelam (Current Nutrition & Food Science, 2024)
The coronavirus disease (COVID-19) came to be an epidemic that has occurred at the expense of the health of people. This disease reveals it can be lethal. Aged people and people with other medical occurrences may be more susceptible and become remarkably ill. The existing pandemic situation mandates scientific vigilance, hence we exploration to medicinal plants like Curcuma longa, Azadirachta indica, Ocimum sanctum, Tinospora cordifolia, Triphala, Phyllanthus emblica, Aloe barbadensis, Syzygium aromaticum, Cinnamomum verum, Allium cepa, Zingiber officinale, Piper nigrum, Allium sativum. The holistic Indian therapeutic system prescription is acknowledged as “Ayurveda”. Natural herbal remedies show more effectiveness which is moving towards the present day with the help of traditional medicine. The factual of the Immunity booster is to determine components of natural lineage have an antiviral outcome. This booster helps to prevent humans from infection caused by SARS-CoV-2. The molecular docking technique is used to disclose the interaction between molecules which is already researched, and the protein. In conclusion, the identified natural compounds from medicinal plants act as an herbal booster for increasing immunity in contradiction to SARS-CoV-2 contagion in patients.
Keywords: medicinal plants